ЕЛЕКТРОФІЗИЧНІ ПРОЦЕСИ РОЗВИТКУ ЛАВИН ЕЛЕКТРОНІВ В ПОВІТРІ У ПРИСТРОЇ ІМПУЛЬСНОГО ДІЕЛЕКТРИЧНОГО БАР’ЄРНОГО РОЗРЯДУ - Vasetsky, Yu.M. (Інститут електродинаміки НАН України, Київ, 2025)
The purpose of the work is to study the influence of the size of the discharge gap and the time dependence of the increase in the pulsed electric field to the characteristics of the avalanche stage of a pulse dielectric barrier discharge (PDBD) from the beginning of electron drift in increasing electric field, taking into account the threshold nature of the impact ionization process in the gas, the influence of photo-ionization to the enlargement of avalanches, diffusion and electrostatic repulsion of electrons at the head of the avalanche. Computational studies were carried out for the specific electrode system with the dielectric barrier located on the cathode for gas gaps 1–3 mm, voltage pulse with the amplitude of 25 kV and time of its achievement of 50 ns. It is established that after three or four stages, the electric field strength of the avalanche-streamer transition has a value of 80-100 kV/cm, which occurs ~30 ns after the voltage is applied, and weakly depends on the size of the gas gap. For the test experiment with gap of 1.5 mm, such values occur at the moment of reaching the maximum current value. It is determined that the size of the electron avalanche for the given voltage pulse in the PDBD is determined by the process of electron diffusion. It is shown that after applying voltage as a result of the first stage of electron drift, the number of emitted photons capable of generating effective electrons for the further development of the avalanche process strongly depends on the size of the discharge gap. The limits of the discharge gaps with significantly different possibilities to initiate the avalanches at subsequent stages are determined. References 22, figures 9, tables 2.